An Analysis of figurative Language in Banda Neira’s Album Yang Patah Tumbuh, Yang Hilang Berganti - Maghfirah Fitri MG; Kismullah Kismullah; Chairina Nasir (Research in English and Education Journal, 2022)
Figurative language is a way of expressing language feelings. This research discusses the analysis of figurative language in Banda Neira’s album yang patah tumbuh, yang hilang berganti. The purpose of this study to determine the types of the figurative language contained in the album. Besides, the researcher also explained the real meaning, the message contained in the song and mentioned the theme of each song. The source is taken from Banda Neira's album "Yang patah tumbuh, yang hilang berganti". The research design used in this research is qualitative research with document analysis as a data collection technique. From the analysis that has been done, it was found 40 figurative languages contained in the five songs selected in the album. The figurative language found in this study is categorized based on the Keraf framework (2007). The data found were metaphor (7 data), personification (10 data), metonymy (7 data), allegory (2 data), epithet (8 data), synecdoche (3 data), antonomasia (1 data), allusion (1 data), and hypalase (1 data). Meaning is important in understanding the content of song lyrics. If the listener can understand the meaning of the song, the message can be conveyed. This research can help readers to understand the types of figurative language, especially understanding the meaning and message contained in the Banda Neira album "Yang patah tumbuh, yang hilang berganti".